Origin of power fluctuations in GaN resonant-cavity light-emitting diodes - Bradley, Louise; Roycroft, Brendan; Akhter, Mahbub; Maaskant, Pleun; Corbett, Brian; Shaw, Alan; de Mierry, Phillipe; Poisson, Marie-Antoinette (My University, 2004)
Resonant-cavity light-emitting diodes (RCLEDs) with multiple InGaN/GaN quantum wells have been grown on sapphire substrates. The emission was through the substrate, and the top contact consisted of a highly reflecting Pd/Ag metallization. The peak emission wavelength was measured to be 490 nm. Under constant current biasing, the intensity was observed to fluctuate irregularly accompanied by correlated variations in the voltage. To investigate this further, emission from the RCLED was focused through a GaAs wafer onto a Vidicon camera. This gave a series of infrared, near-field images, spectrally integrated over a wavelength range from 870 nm to 1.9 µm. Flashes from point sources on the RCLED surface were observed, indicating that short-lived, highly localized “hot spots” were being formed that generated pulses of thermal radiation. It is proposed that this phenomenon results from the migration of metal into nanopipes present in this material. The filled pipes form short circuits that subsequently fuse and are detected by bursts of infrared radiation that are recorded in real time.
PUBLISHED
Keywords: Semiconductor materials; Light emitting diodes; Laser materials